PENINGKATAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA DENGAN MODEL PEMBELAJARAN ADVANCE ORGANIZER PADA POKOK BAHASAN TRIGONOMETRI - Risnaini Mei Sucianti (LPPM Universitas Bina Bangsa, 2022)
The background of this research is the low student activity that affects the low learning outcomes of class X SMA Bosowa Al-Azhar. One alternative to overcome learning problems that occur is to apply the advance organizer learning model. This advance organizer model is assisted by the preparation of a concept map. The purpose of preparing a concept map is for students to be able to show the relationship between the various components of concepts and ideas. Overall, learning using the advance organizer learning model using concept maps has an impact on increasing students' mathematics learning activities so that they can improve student learning outcomes. This study uses a qualitative approach with the type of classroom action research, which consists of four stages that form a cycle, namely planning, implementing, observing, and reflecting. The research was conducted in class X SMA Bosowa Al-Azhar, with 10 students. Based on the research that has been done, students' mathematics learning outcomes have increased. The average of the final tests in cycle I was 53,2, in cycle II was 71,4 and in cycle III was 81,1. The percentage of students who achieved KKM scores (Minimum Passing Criteria) in cycle I was 20%, in cycle II was 50% and in cycle III was 80%. Based on the results of the study it can be concluded that: (1) The advance organizer learning model using concept maps can increase student learning activities during the learning process. (2) The advance organizer learning model using concept maps can improve students' mathematics learning outcomes